An ultra-massive white dwarf with a mixed hydrogen–carbon atmosphere as a likely merger remnant - Hollands, M. A. (2020)
White dwarfs are dense, cooling stellar embers consisting mostly of carbon and oxygen, or oxygen and neon (with a few per cent carbon) at higher initial stellar masses. These stellar cores are enveloped by a shell of helium, which in turn, is usually surrounded by a layer of hydrogen, generally prohibiting direct observation of the interior composition. However, carbon is observed at the surface of a sizeable fraction of white dwarfs, sometimes with traces of oxygen, and is thought to be dredged up from the core by a deep helium convection zone. In these objects, only traces of hydrogen are found, as large masses of hydrogen are predicted to inhibit hydrogen-helium convective mixing within the envelope. We report the identification of WD J055134.612+413531.09, an ultra-massive (1.14 solar masses (M☉)) white dwarf with a unique carbon-hydrogen mixed atmosphere (atomic ratio C/H = 0.15). Our analysis of the envelope and interior indicates that the total hydrogen and helium mass fractions must be several orders of magnitude lower than predictions of single-star evolution: less than 10-9.5 and 10-7.0, respectively. Due to the fast kinematics (129 ± 5 km s-1 relative to the local standard of rest), large mass and peculiar envelope composition, we argue that WD J0551+4135 is consistent with formation from the merger of two white dwarfs in a tight binary system.